2011
DOI: 10.1111/j.1745-4549.2011.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

1h NMR Investigation of Oil Oxidation in Macadamia Nuts Coated With Zein-Based Films

Abstract: The effectiveness of corn‐zein edible coatings in blocking oil oxidation on macadamia nuts was studied by using high‐resolution Hydrogen Nuclear Magnetic Resonance (1H NMR) spectroscopy. Formulations with a zein concentration of 4.0% by weight and oleic acid (OA) as a plasticizer in different proportions were evaluated. Accelerated oxidation was conducted by using an O2‐reactor in a 60C water bath. The oil extracted from the nuts at the beginning of the study and after 10 and 30 days into the experiment were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
9
0
6
Order By: Relevance
“…Essas alterações estruturais reduzem as propriedades de barreira e a aderência (ASSIS e SILVA, 2003), e facilitam a proliferação de fungos. Assim, elevadas adições de plastifi cantes devem ser evitadas, as quais, muitas vezes, inviabilizam o uso da formulação como formadora de cobertura protetora (COLZATO et al, 2011).…”
Section: Deposição E Formação De Fi Lme Superfi Cialunclassified
See 1 more Smart Citation
“…Essas alterações estruturais reduzem as propriedades de barreira e a aderência (ASSIS e SILVA, 2003), e facilitam a proliferação de fungos. Assim, elevadas adições de plastifi cantes devem ser evitadas, as quais, muitas vezes, inviabilizam o uso da formulação como formadora de cobertura protetora (COLZATO et al, 2011).…”
Section: Deposição E Formação De Fi Lme Superfi Cialunclassified
“…Embora o uso de pincel (HARALAMPU, 1990;CHLEBOWSKA-SMIGIEL et al, 2007) e o spray também tenham sido utilizados para alguns casos (ANDRADE et al, 2012), a imersão é o procedimento que garante que toda a superfície entre em contato com a solução fi lmogênica e uma leve agitação permite o desprendimento de bolhas, possibilitando uma deposição mais homogênea. Uma sequência lógica de formação de cobertura pode então ser resumida segundo o esquema ilustrativo da Figura 3.…”
Section: Modos De Aplicaçãounclassified
“…However, that is a very expensive methodology and requires special skills to interpret the spectra. The use of 1 H and 13 C NMR spectroscopy in food, applied by different research groups [138][139][140][141][142][143][144][145][146], has proved to be very useful in evaluating the oxidative status of the lipid fraction, as well as in providing information on the nature (main functional groups) and concentration of the compounds found (i.e. hydroperoxides, carbonyl compounds and dienes).…”
Section: Magnetic Resonancementioning
confidence: 99%
“…At the end of storage period, decreases of 18%, 30%, and 38% were noted in K 232 values of HCZE, HCZ, and HCZT samples, respectively, compared to control. In their study, Colzato et al () showed that conjugated dienes were the major products in macadamia nuts underwent accelerated oxidation assay. At the end of storage period, K 270 value of uncoated hazelnut samples increased gradually up to 0.61 while that of coated samples was around 0.2–0.3.…”
Section: Resultsmentioning
confidence: 99%